Analysis of Factors Causing Initial Reading Difficulties of Grade I Students of SD Negeri 29 Sanggau - Septiani, Jumilah; Afryaningsih, Yunika; Nurcahyo, Muhammad Agmal (Lembaga Penelitian dan Pendidikan Mandala, 2023)
This study aims to describe the shape, shape and factors causing initial reading difficulties of grade I students of SDN 29 Sanggau. This research uses a qualitative approach with a type of descriptive research and the subject is a class teacher, a grade I student of SDN 29 Sanggau. Data collection is carried out by interviews, observations and egra tests. Data analysis techniques use the Miles and Huberman model, namely data reduction, data display and data verification. The results of the observation and EGRA test of initial reading difficulties of grade I students of SDN 29 Sanggau, researchers concluded that of the 5 difficulties in the initial reading aspect, namely the aspect of recognizing letters from 2 aspects, namely the aspect of recognizing capital letters, 5 students could not mention capital letters. 4 students are not familiar with letters much and it is difficult to distinguish almost the same letters. In this aspect, the average score obtained is 71.4 and the percentage is 36%. Aspects of recognizing lowercase letters 4 students have not been able to pronounce lowercase letters. 4 students are not familiar with letters much and it is difficult to distinguish letters that are almost the same, namely. In this aspect, the average score obtained is 74.36 and the percentage is 32%. The aspect of reading words from 3 aspects, namely the aspect of identifying letters 9, students cannot identify letters. In this aspect, the average score obtained is 80.5 and the percentage is 36%. The aspect of stringing words is 15 students have not been able to string together words. In this aspect, the average score obtained is 66.1 and the percentage is 56%. Aspect of identifying words 5 students cannot identify words yet and need teacher help. 4 students said the wrong word. 6 students remove letters and change words with similar ones. In this aspect, the average score obtained is 67.2 and the percentage is 60%. The aspect of reading words that have no meaning from 3 aspects, namely the aspect of identifying letters 9, students cannot identify letters. In this aspect, the average score obtained is 80.5 and the percentage is 36%. Aspect of stringing the arrangement Aspect of word fluency 3 students are not fluent in stringing words. 2 students have not yet assembled the arrangement of the letters ng. In this aspect, the average score obtained is 62.5 and the percentage is 60%. Aspect of identifying the word 5 students pronounce the wrong word. 2 students omit letters and 2 students change words with similar ones. In this aspect, the average score obtained is 63.9 and the percentage is 60%. Aspects of fluency in reading aloud and reading comprehension from 5 aspects, namely the aspect of identifying letters 9 students have not been able to identify letters. In this aspect, the average score obtained is 80.5 and the percentage is 36%. Aspect of stringing word arrangement 7 students cannot string together words and still need teacher help. 3 students stammered in stringing together the wording. 3 students are not fluent in stringing words. 2 students have not yet assembled the arrangement of the letters ng and ny. In this aspect, the average score obtained is 60.89 and the percentage is 60%. Aspect of identifying words 7 students cannot identify words yet and need teacher help. 5 students pronounce the word incorrectly. 2 students omit letters and 2 students change words with similar ones. In this aspect, the average score obtained is 62.31 and the percentage is 60%. The reading fluency aspect of 3 students is not fluent in reading and needs teacher help. 12 students read with spelling, too long and faltering. In this aspect, the average score obtained is 62.01 and the percentage is 60%. The aspect of the ability to answer questions about the content of reading 5 students cannot answer the questions. 6 original students in answering the questions. 2 students answered two questions incorrectly. In this aspect, the average score obtained is 64.32 and the percentage is 52%. Listening aspect (listening comprehension) from 2 aspects, namely the aspect of listening attentively 7 students do not focus on listening to stories. 5 students lack focus on hearing stories. In this aspect, the average score obtained is 71.76 and the percentage is 48%. The aspect of the ability to answer questions about the text listened to 5 students could not answer the questions. 6 original students in answering the questions. 2 students answered two questions incorrectly. In this aspect, the average score obtained is 65.52 and the percentage is 52%. The results of student interviews caused the initial reading difficulties of grade I students of SD 29 Sanggau were Physiological Factors with a percentage of 12%, Intellectual Factors with a percentage of 12%, Environmental Factors, with a percentage of 16%. Motivation Factor with a percentage of 24% and Confidence with a percentage of 4%.